The Study into Theoretical and Methodological Readiness of Defectology Students to Pursue Master Degree Programmes - Alla V. Zakrepina; Elena A. Shilova; Elena A. Strebeleva (National Research Mordova State University, 2021)
Introduction.Training a competitive specialist at the level of a master program is an important educational goal. The problem of the continuity of educational levels as a condition for the quality of graduate training is debatable, because the focus of such discussions is often around the methodological components of the educational program, rather than the conceptual guidelines for professional growth. The aim of the research was to study the level of studentsʼ readiness to follow master degree programs in the field of special (defectological) education. Materials and Methods. The research constitutes a theoretical analysis of the problem of readiness of defectology students to pursue the master degree level of education. In the course of empirical research, the results of a questionnaire and self-assessment were used. The survey included 68 master degree students of 4 master degree programs. Statistical processing of the results was carried out using the Statistica 10.0 software package for the Windows. Results. The authors found that the target guidelines for the reconstruction of the professional training of master students in the field of special (defectological) education is a set of expected knowledge, skills, and abilities from the standpoint of modern requirements and social need for the activities of a specialist in the changing conditions of education, upbringing and development of children with disabilities; the designing of a master program requires the actualization of theoretical and methodological training, taking into account its extrapolation to the level of implementation of applied professional competencies in accordance with the modern needs of society and the dynamics of the educational labor market. Discussion and Conclusion. The results obtained facilitate the development of professional training of master students in the field of special (defectological) education and allow us to consider theoretical and methodological readiness to pursue a master course in terms of continuity of educational tasks and the continuity of educational levels that make up the fundamental principles for the preparation of a competitive graduate.